Memoria y muerte. La dictadura de Pinochet en las películas de Pablo Larraín: Tony Manero (2007) y Post Mortem (2010) - Tzvi Tal (Centre de Recherches sur les Mondes Américains, 2012)
The hegemonic memory of the seizure of power in Chile by the rebellion of General Augusto Pinochet, manifests a symmetrical ambivalent vision that supports the continuity under democracy of the neoliberal project imposed by the dictatorship. The films of Pablo Larraín, Tony Manero (2007) and Post Mortem (2010), well received by critics and international festivals, did not had a public success in Chile. Despite they are consistent with the hegemonic discourse about memory, both violate the inclination to oblivion violence prioritized by it.